2015
DOI: 10.1093/neuonc/nov197
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatosis cerebri: a rare form of primary central nervous system lymphoma. Analysis of 7 cases and systematic review of the literature

Abstract: LC is a misdiagnosed entity associated with considerable diagnostic delay. MRI evidence of bilateral hemispheric involvement and CSF pleocytosis should be alerts for this diagnosis. Treatment with methotrexate-based chemotherapy must be considered, especially for patients with good KPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 45 publications
6
66
0
9
Order By: Relevance
“…However, other reports have demonstrated that more than 50% of 42 patients had lymphomatosis identified in the basal ganglia with concurrent supratentorial and infratentorial lesions as well as bilateral hemispheric lesions 7. They are not associated with a mass effect.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, other reports have demonstrated that more than 50% of 42 patients had lymphomatosis identified in the basal ganglia with concurrent supratentorial and infratentorial lesions as well as bilateral hemispheric lesions 7. They are not associated with a mass effect.…”
Section: Discussionmentioning
confidence: 89%
“…The 5-year survival after combined chemotherapy and radiation therapy for PCNSL was reported in one report to be 32% 18. However, in a recent series of LC cases, 47.2% of patients did not survive past 3 months after the onset of symptoms 7. They found that a high Karnofsky score ≥70 and treatment with methotrexate was associated with improved survival and that T-cell LC is an independent poor prognostic factor.…”
Section: Discussionmentioning
confidence: 95%
“…Até o momento, na literatura médica há apenas 27 artigos que se referem diretamente à linfomatose cerebral, descrevendo um total de 44 indivíduos com esta doença 5,6,8 .…”
Section: Bakshi Et Al 1 Descreveram Dois Casos De Indivíduos Com Demunclassified
“…A maior parte dos indivíduos são europeus (43,2%), seguidos pelos asiáticos (34,1%) e, por último, norte-americanos e canadenses (22,7%). Apenas raramente os indivíduos são imunossuprimidos (6,8%) 5,6,8 . Nossa paciente era do gênero feminino, dentro da faixa etária descrita e imunocompetente.…”
Section: Aspectos Demográficosunclassified
See 1 more Smart Citation